Indications of the strength and weakness of the linguistic sounds in the rain song poem by Al-Sayyab Analytical descriptive study - Ahmed, Narmeen Ghalib (Journal of Arabic Language Sciences and Literature, 2023)
This study is based on the concept of strength and weakness in the sounds of Arabic in several aspects, including: the strength of aural clarity that characterizes the sounds of Arabic, and then the muscular effort exerted by the vocal apparatus during the pronunciation of each sound, and this aspect was precisely explained by the ancient Arabic scholars during their speeches. The letters, their characteristics, and images of dealing with them in the context, and indicating the predominance of the strongest sound in phonemic transactions, and the ancient modernists agreed, but they added other elements that increase its strength, including: the strength of the site, the stability of the sound and its temporal extension. In addition to supra-syllabic units such as accent and intonation; And its connection with the rising and falling of the voice in the syllables of the word or the context of the sentences, and the harmony between the nature of these sounds and the meaning they reflect on the context of the text in a highly literary manner, which we will follow in our research - an analysis and description - of the poem The Rain Song of Sayyab.